Ocular tolerance in rabbits after intracameral administration of a fixed combination of tropicamide, phenylephrine, and lidocaine with and without rinsing. Issue 5 (May 2017) - Nuijts, Rudy M.M.A.; Mencucci, Rita; Viaud‐Quentric, Karen; Elena, Pierre‐Paul; Olmière, Céline; Behndig, Anders
Abstract : Purpose : To evaluate the safety and tolerability of a single intracameral administration of a combined mydriatic (tropicamide and phenylephrine) and anesthetic (lidocaine) formulation (Mydrane) with or without rinsing. Setting : Iris Pharma, La Gaude, France. Design : Experimental study. Methods : Sixty pigmented rabbits received 100 μL or 200 μL of the combination product or a placebo (sodium chloride 0.9%) by intracameral injection. For the combination product, separate groups were included with and without rinsing after administration. From day 1 day to day 7, assessments included general clinical and ocular observations, pupil diameter measurements, corneal assessments, confocal microscopy, and electroretinography (ERG). Necropsy examinations were performed at study completion at day 8. Results : Rapid mydriasis, stable 24 minutes after injection and returning to baseline levels by day 1, was induced in all groups that received the combination mydriatic and anesthetic drug. Rinsing had no effect. The combination product induced no adverse effects on the anterior or posterior segment of the eye (ie, no increased corneal thickness and endothelial cell loss, no abnormalities in ERG). Slitlamp examination showed slightly increased anterior chamber inflammation with rinsing in both the study group and placebo group. This observation was not confirmed by aqueous flare examination. No toxic effects of the products were found on histological evaluation. Conclusion : The combination mydriatic and anesthetic drug administered to pigmented rabbits as a single intracameral injection at volumes of 100 μL and 200 μL was well tolerated with no ocular adverse effects and no effect on the corneal endothelium.